Why is there a gender earnings gap in self-employment? A decomposition analysis with German data - Daniel S. J. Lechmann; Claus Schnabel (IZA Journal of European Labor Studies, 2012)
Using a large data set for Germany, we show that both the raw and the unexplained gender earnings gap are higher in self-employment than in paid employment. Applying an Oaxaca-Blinder decomposition, about one quarter to one third of the difference in monthly self-employment earnings can be traced back to women working fewer hours than men whereas there are no robust segregation effects. Working time flexibility and career aspirations do not seem to contribute much to the gender earnings gap, whereas family background plays a certain role as it affects the earnings of self-employed men and women quite differently.
Keywords: J31; J71; 330; earnings differential; gender pay gap; Germany; self-employment; Selbstständige; Lohnstruktur; Geschlecht; Deutschland